Pembinaan Masyarakat dengan Pelatihan Aplikasi Design Produk dalam Peningkatan Pemasaran dan Industri Kreatif - Fajrin, Alfannisa; Elisa, Erlin (ASOSIASI IDEBAHASA KEPRI, 2025)
In a business, personal branding is an important thing to attract consumers. One effort to attract consumer attention is to create a unique and attractive product design. In addition to physical marketing, in the creative industry world, utilizing advertising via the web or social media is very helpful in finding customers, of course with an attractive appearance. With a good product design, it will influence consumers to buy a product. That is why product design is one of the important sub-sectors of the creative economy. One of them is Delico, a creative industry built by young millennials in Batam. At the beginning of its establishment, Delico was still unable to attract the attention of consumers because it had a product design that was not so good because it still used applications that were not specifically for design. In making a design, brand owners cannot just do it. Product design must be adjusted to the target market being targeted. Customers must have their own characters, from color, graphics, illustrations to design layout. This is what makes the prospect of this service to help this business sector increasingly attract customers or consumers by mastering one of the design applications.